Weather forecasting on parallel architectures - Sela, J.G. (Parallel computing, 1995)
Global forecasting at the National Meteorological Center is performed using a spherical harmonics spectral model. The model is used in global data assimilation, and in the aviation and medium range forecast production suites. In this presentation, the major numerical and physical aspects of the model are highlighted, and parallelization considerations are analyzed and applied to three parallel computer architectures. The first parallelization is on a parallel vector processor shared memory platform such as Cray YMP or C90. The other two are on distributed memory platforms: a data parallel implementation on Connection Machines and a single program multiple data (SPMD) adaptation to a Cray T3D machine.